Implementasi Berbasis Undang – Undang 1945 Sebagai Transformasi Teknologi dalam Meningkatkan Strategi Perdagangan dan Pemasaran Industri Migas Yang Bersifat Dinamis - Edy Soesanto; Angelicleatemia Angelicleatemia; Nona Julia (Jurnal Bisnis Inovatif dan Digital, 2024)
The purpose of this research is to examine implementation based on the Law (1945) as a technological change in improving business dynamics and marketing strategies for the oil and gas industry. This study examines document analysis as a research method. The research results show that the enactment of the Law (1945) opened up new opportunities in technological change which changed the business and marketing strategy paradigm of the oil and gas industry to better adapt to market and technological dynamics. These findings provide valuable information to stakeholders to develop responsive and innovative strategies to meet the challenges of the growth of the oil and gas industry.